2004
DOI: 10.1093/chemse/bjh061
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the Odor Stick Identification Test for Japanese Patients with Olfactory Dysfunction

Abstract: The odor stick identification test (OSIT) is a new test of olfactory function recently developed for Japanese people. The purpose of the present study was to evaluate this test in relation to T&T olfactometry and the cross-cultural smell identification test (CC-SIT) by applying to 110 Japanese patients with olfactory disturbance. The averaged recognition thresholds for five odorants in T&T olfactometry, the number of correct answers in the CC-SIT and the rates of identification of 13 odorants in the OSIT were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(32 citation statements)
references
References 8 publications
1
29
0
Order By: Relevance
“…The identification ratio of Japanese orange was 40% in normal subjects, and 31.5% in PD, respectively in our study. Previous studies showed that the identification ratio of Japanese orange was lowest in normal subjects (26,27), and was below 70% in normal subjects aged from 20 to 80 years, and was also lower in patients with olfactory dysfunction (28) because subjects chose "apple" in error (26,28). In the present study, the reason why the identification ratio of Japanese orange in normal subjects was lower than that in the previous studies was that the age of normal subjects was older (mean age 69.7 years).…”
Section: F I G U R E 1 Co Mp a R I S O N O F C O R R E C T O D O R mentioning
confidence: 91%
See 2 more Smart Citations
“…The identification ratio of Japanese orange was 40% in normal subjects, and 31.5% in PD, respectively in our study. Previous studies showed that the identification ratio of Japanese orange was lowest in normal subjects (26,27), and was below 70% in normal subjects aged from 20 to 80 years, and was also lower in patients with olfactory dysfunction (28) because subjects chose "apple" in error (26,28). In the present study, the reason why the identification ratio of Japanese orange in normal subjects was lower than that in the previous studies was that the age of normal subjects was older (mean age 69.7 years).…”
Section: F I G U R E 1 Co Mp a R I S O N O F C O R R E C T O D O R mentioning
confidence: 91%
“…Recently, the odor stick identification test for Japanese (OSIT-J) was developed by Saito, Ayabe-Kanamura (25,26) as a new type of smell identification test; it consists of 13 odorants that are all familiar to Japanese subjects. A significant correlation coefficient between the identification rate of OSIT-J score and the results of T&T olfactometry has been reported both in normal Japanese subjects and in patients with olfactory disturbances (27,28). The OSIT score has been shown to be significantly correlated with the CC-SIT score, but the average identification rate using the OSIT was significantly higher than that using the CC-SIT (26 …”
Section: Employed the 40-odorant University Of Pennsylvania Smell Idmentioning
confidence: 96%
See 1 more Smart Citation
“…Among such tests are the 40-odor University of Pennsylvania Smell Identification Test (UPSIT; known commercially as the Smell Identification Test TM or SIT) (Doty et al 1984b), the 12-odor Brief-Smell Identification Test TM (B-SIT; also known as the Cross-Cultural Smell Identification Test TM ) (Doty et al 1996;Liu et al 1995), the 3-odor Pocket Smell Test TM (PST; Duff et al 2002), and a recent variant, the Quick Smell Identification Test TM (Q-SIT) (Jackman and Doty 2005), the 12-item Odor Memory Test TM (OMT) (Choudhury et al 2003), the San Diego Odor Identification Test (Anderson et al 1992), the Scandinavian Odor Identification Test (SOIT) (Nordin et al 1999), the Odor Stick Identification Test (Hashimoto et al 2004), the ''Sniff 'n Sticks'' test (Kobal et al 1996), the Viennese Olfactory Test Battery (Lehrner and Deecke 1999), and an 8-odor identification test employing polyester diskettes (Simmen et al 1999).…”
Section: Odor Identification Testsmentioning
confidence: 99%
“…7,8 This test is simple, can be administered quickly, and has been validated for olfactory testing of Japanese patients with olfactory dysfunction. 9,10 We have previously shown 6 that the OSIT-J can be administered to US subjects with a normal sense of smell, despite the unfamiliarity of these subjects with some of the odors used in the test. However, cross-cultural clinical applicability of this test in evaluating patients with olfactory dysfunction has not been demonstrated.…”
mentioning
confidence: 99%